Teaching and Learning in Small Groups - Maryam Aalaa; Maryam Peimani; Mitra Gharib (مجله ایرانی آموزش در علوم پزشکی, 2013)
In recent decades, there have been numerous attempts to define precisely what is meant by small group teaching. Many writers argue that small group teaching method is among the most difficult and highly skilled of teaching techniques, in which in addition to the primary objective of teaching students to think, the tutor must have a number of subsidiary objectives if the small group is to function. In other words, the interpersonal and interactive nature of small groups makes them a challenging and appropriate vehicle for engaging students in their own learning. However, not only do tutors have to learn how to teach using small group methods but students also have to learn how to work in small groups. On the other hand, nowadays it is not only that there are more students participating in higher education than before it is also the case that students are coming from more diverse backgrounds, so inclusion and internationalization are matters to concern ourselves with, and there is a need for providing a more diversified curriculum, that they are responsible not only for what is taught but also, in part, for how students learn. These entire changes mean that the small group is now seen as a means of fostering student engagement, cooperative and collaborative learning. Planning for effective small group teaching is as important as planning any other teaching activity. This point sometimes goes unrecognized because learning in small groups can at first glance appear unstructured. Some lecturers are put off by the seemingly informal, loose or open-ended nature of small group learning, or they fear this informality will be a recipe for chaos, whereas behind the facade of the informal group lies a backdrop in which all the learners are playing within a known set of rules which are spoken or unspoken. In this paper, after the introduction of the context and features of small groups, the necessity of planning for this teaching method is mentioned. Moreover, stages of group development and management as well as the teaching - learning nature in small groups are described. Next, the teacher and learner skills needed for teaching and learning in small groups and other qualifications required to teach in a small group, such as instructional space group, and the use of small groups in clinical and medical education are offered.